Valorização de resíduos da serragem de madeira de eucalipto a partir da aplicação da pirólise - Missau, Juliano (2022)
The present work focused on adding value to the sawdust of eucalypt wood, which is a lignocellulosic waste. This was accomplished by applying the pyrolysis technique, converting sawdust into biochar. The solid products (biochar) obtained from pyrolysis were investigated regarding their application as briquettes (energy purposes) and as adsorbent material. In the first stage of the work, the biochar was mixed with other binder residues such as crude wax (polymer pyrolysis residues) and eucalypt leaves, in the presence of starch, to produce briquettes. The briquettes were analyzed for their higher heating value (HHV) and mechanical strength. The biochar yield obtained in the pyrolysis was 35%, and its HHV was 33.02 MJ/kg at 400 ºC. The proportions of residues (crude wax and/or eucalypt leaf) evaluated in the composition of biochar briquettes were 10, 20 and 30%. The proportion of corn starch was set at 8%. The briquettes with 30% crude wax showed the best HHV, 23.45 MJ/kg, and the highest mechanical resistance to the shatter index test, 97.81%. In summary, briquettes with high energy efficiency and durability were produced. In the second stage of the work, the biochar was chemically activated with phosphoric acid (40%) and impregnated with calcium and aluminum lamellar double hydroxides (Ca/Al LDH), to improve its adsorption capacity. The novel developed adsorbent material was applied to remove the crystal violet (CV) dye from aqueous solutions through the batch adsorption operation. The adsorbent characterization results suggested that the material was effectively synthesized and supported in the biochar. Furthermore, the adsorption experiments indicated that pH 8 was more suitable for adsorption of the CV dye. In the adsorption kinetics and isotherm, the experimental data fit better to the pseudo-second order kinetic model and to the Freundlich isothermal model, respectively. The newly developed adsorbent showed a high adsorption capacity of the CV dye of 496.55 mg·g−1 at 50°C. Regarding the thermodynamic properties, the use of this adsorbent demonstrated a favorable, spontaneous and endothermic process. In the adsorption and desorption cycles, this new adsorbent material maintained 71% of the initial adsorptive capacity, even after four cycles of reuse. Therefore, the new biochar, chemically activated with phosphoric acid (40%) and impregnated with Ca/Al LDH, produced generated a sustainable adsorbent with high performance for the treatment of effluents contaminated by dyes.